La corrispondenza di Giovanni Della Casa: stato dell'arte, progetti (e dieci inediti) (Quaderni di Gargnano, 2018)
The paper takes stock of the bibliographic scholarship on the correspondence of Giovanni Della Casa. It reviews Della Casa's published and unpublished letters and looks at the current state of ongoing research. The paper also lays out the results of the scholarship conducted by the author for the preparation of the section in the Autografi dei letterati italiani and the appendix includes the text of and a commentary on ten hitherto unpublished letters
Keywords: Giovanni della Casa; inediti; corrispondenza; lettere; manoscritti